Upgrading Bio-Fuel from Jatropha Oil via Onepot Transesterification-Isomerisation Using Solid Acid Catalysts - Dewi Wahyu Narulita; Murayama Hitomi; Mutamima Anisa; Purnama Indra (E3S Web of Conferences)
This study used transesterification-isomerisation processes to synthesise biodiesel from non-edible vegetable oils, specifically jatropha oil and palm fatty acid distillate (PFAD). To facilitate the separation of products, both were conducted in a batch reactor with a solid acid catalyst. Additionally, a one-pot isomerisation reaction was carried out to improve the cold flow properties of the biodiesel by reducing its cloud point. The skeletal isomerisation results showed a significant variation in the conversion rate of methyl oleate, ranging from 0% to 100% at 250°C, depending on the catalyst used. Al-SBA-15 achieved a 100% conversion rate at 250°C, significantly reducing the biodiesel cloud point. The esterification reaction results indicated that the conversion rate of fatty acids was 100% at 150°C when either MPS (sulfonic SBA-15) or Al-SBA-15 catalysts were used. Moreover, by increasing the skeletal isomer product, the viscosity and melting point of upgraded bio-oil can be decreased.